Asplenia in a patient with Fanconi's anemia-like congenital aplastic anemia - Erduran, Erol; Ökten, Ayşenür; Kaya, Gülay; Yıldıran, Alişan (The Turkish Journal of Pediatrics, 2000)
Fanconi's anemia (FA) is an autosomal recessive disease manifested by pancytopenia resulting from bone marrow failure, variable physical anomalies and cancer susceptibility. A seven-year-old girl with Fanconi's anemia-like congenital aplastic anemia and concurrent asplenia without the congenital heart defects or the abdominal heterotaxia is reported. Asplenia was indicated using denatured red cells labelled with 51 Cr, abdominal ultrasonography and computerized tomography. Immunological studies showed immunoglobulins (IgG, IgA, IgM), C_3 and C_4 levels within normal limits and the percentage of CD_3 , and C_4 cells and the CD_4/CD_8 ratio decreased. The patient had not been exposed to recurrent pneumococcal infections. We think that isolated asplenia may occur in patients with Fanconi's anemia-like congenital aplastic anemia without the congenital heart diseases or abdominal heterotaxia.
Keywords: asplenia; Fanconi's anemia-like congenital aplastic anemia